1999
DOI: 10.1117/12.357671
|View full text |Cite
|
Sign up to set email alerts
|

<title>MSTAR's extensible search engine and model-based inferencing toolkit</title>

Abstract: The DARPA/AFRL "Moving and Stationary Target Acquisition and Recognition" (MSTAR) program is developing a modelbased vision approach to Synthetic Aperture Radar (SAR) Automatic Target Recognition (ATR). The motivation for this work is to develop a high performance ATR capability that can identify ground targets in highly unconstrained imaging scenarios that include variable image acquisition geometry, arbitrary target pose and configuration state, differences in target deployment situation, and strong mtra-cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Previous studies using SAR data have demonstrated the existence of persistent scatterers 18 . These scatterers reflect radiation back to the sensor over an extended range of view angles.…”
Section: The Treatment Of Anisotropic Scatterersmentioning
confidence: 99%
“…Previous studies using SAR data have demonstrated the existence of persistent scatterers 18 . These scatterers reflect radiation back to the sensor over an extended range of view angles.…”
Section: The Treatment Of Anisotropic Scatterersmentioning
confidence: 99%
“…Some form of confidence indication is especially important for machine consumption of ATR products, for example by a fusion system. This particular ATR modeling effort was part of a study of decision-level fusion algorithms (the AFRL/SNA Fusion for Identifying Targets Experiment (FITE) [7,8]). Currently, FITE supports ATR models for two types of ATR algorithms, and these are SAR-based (this article) and IR-based [9].…”
Section: Atr Performance Modelsmentioning
confidence: 99%
“…There are no real SAR data with occluded objects available to the general public (limited data on vehicles in revetments [14] and partially hidden behind walls [19] has been reported to exist, but it has not yet been released for unrestricted use). In addition, there is no standard, accepted method for characterizing or simulating occluded targets.…”
Section: Target Occlusionmentioning
confidence: 99%
“…Some of the SAR recognition techniques, e.g., MINACE filters [6], PERFORM [10], mean squared error template matching [14] and invariant histograms [9] have reported limited test results for small amounts of occlusion, typically 25 percent or less. In addition, the developers of the MSTAR search engine reported [19] using a shadow inferencing technique to hypothesize targets with up to 30 percent occlusion in the cross-range direction.…”
Section: Introductionmentioning
confidence: 99%